Pelatihan Penggunaan Media Wordwall Bagi Guru SDN 17 Bajoe Kecamatan Tanete Riattang Timur Kabupaten Bone - Rosmalah; Abd. Hafid; Hardianti Hafid (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2023)
Abstract. The aim of this community engagement initiative is to improve the use of the interactive learning platform Wordwall by instructors at SDN 17 Bajoe, Tanete Riattang Timur Subdistrict, Bone Regency. Wordwall is a digital platform that facilitates more student participation in the classroom. The community engagement team is conducting a training session for the teachers at SDN 17 Bajoe as part of this effort. The course covers Wordwall's core ideas, how to create interactive content, and practical integration techniques for using Wordwall in the classroom. Participants will gain practical advice and hands-on Wordwall training throughout the course, empowering them to create learning products that are more relevant and engaging. The aim of this activity is to help the teachers at SDN 17 Bajoe improve the quality of their instruction and motivate the students to participate more actively in the learning process. As a result, this community engagement program seeks to further the advancement of technology-enhanced learning while providing beneficial outcomes for the local educational community. Keywords: wordwall, learning media, digital era